Literature Review: Hepatocellular Carcinoma (HCC) - Zakiyyah, Luthfi; Fauzan, Muhammad; Gifari, Lalu Maulana Azmi; Faranajhia, Hagia; Putri, Ajeng Ayu; Hermansyah, Anang; Arafah, Tazkiyah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hepatocellular Carcinoma (HCC) is a type of primary liver cancer which is a fatal disease. Globally, Hepatocellular Carcinoma (HCC) is the dominant type of liver cancer, accounting for around 75% of the total incidence. HCC incidents are mostly found in Asia and Africa. In general, the causes of HCC include a history of hepatic cirrhosis, chronic hepatitis B infection, hepatitis C infection, autoimmune hepatitis, excessive alcohol consumption, obesity, smoking, non-alcoholic steatohepatitis (NASH), and diabetes mellitus. There are three types of therapy including surgery, locoregional, and systemic. The therapy is also divided into invasive, minimally invasive, and non-invasive therapy. This literature review aims to facilitate the review of the Hepatocellular Carcinoma. Scientific related questions, databases to be used, selection of keywords, inclusion and exclusion criteria, definition of results and conclusions of selected articles are all elements included in this research search strategy. At the end e met some articles that fit the criteria and conclude that is a deadly disease with high mortality and morbidity because in the early stage HCC is generally asymptomatic.